Indirect comparisons of the efficacy of biological antirheumatic agents in rheumatoid arthritis in patients with an inadequate response to conventional disease-modifying antirheumatic drugs or to an anti-tumour necrosis factor agent: a meta-analysis. Issue 2 (19th November 2010) - Salliot, Carine; Finckh, Axel; Katchamart, Wanruchada; Lu, Yan; Sun, Ye; Bombardier, Claire; Keystone, Edward
Abstract : Background: The availability of increasing numbers of biological agents for the treatment of rheumatoid arthritis (RA) offers several therapeutic options. While all biologicals have proven effective in trials, very limited direct comparisons are available. The objective of the present work was to compare the efficacy of biologicals (anti-tumour necrosis factor (TNF) agents, rituximab, abatacept, tocilizumab) in patients with RA with active disease and (i) an inadequate response (IR) to methotrexate (IR-MTX), (ii) an IR to anti-TNF agents (IR-anti-TNFs) using indirect comparisons. Methods: Randomised clinical trials were identified examining the efficacy of a biological agent in RA at 6 months in patients with an IR-MTX or with an IR-anti-TNF. To compare the relative efficacy of biologicals, adjusted indirect comparison meta-analytic methods to estimate the ORs of achieving a 50% improvement according to American College of Rheumatology criteria (ACR50) response at 6 months were used. Results: A total of 18 published trials and 1 abstract were included in the analyses. In IR-MTX, anti-TNFs had the same probability of reaching an ACR50 compared to 'non-anti-TNF biologicals' taken together (OR 1.30, 95 % CI 0.91 to 1.86). However, when compared to specific biological agents, anti-TNFs demonstrated a higher probability of reaching an ACR50 than abatacept (OR 1.52, 95 % CI 1.0 to 2.28), but not in comparison to rituximab and tocilizumab. In IR-anti-TNF, rituximab demonstrated a higher probability of achieving an ACR50 than tocilizumab (OR 2.61, 95% CI 1.10 to 6.37), but no significant differences existed between rituximab, tocilizumab, abatacept and golimumab. Conclusions: In a meta-analysis of randomised clinical trials of patients with IR-MTX, anti-TNFs demonstrated a higher probability of achieving an ACR50 response than abatacept. In IR-anti-TNF, no difference was found between rituximab, tocimizumab, abatacept and golimumab.